Access to after-hours primary care: a key determinant of children's medical home status - Bing Han; Peggy Guey-Chi Chen; Hao Yu (BMC, 2021)
Abstract Background The medical home (MH) model has been promoted by both the federal and state governments in the United States in recent years. To ascertain American children's MH status, many studies have relied on a large set of survey items, posing a considerable burden on their parents. We aimed to identify individual survey items or domains that best predict MH status for children and use them to develop brief markers of MH status. We also examined whether the identified items differed by status of special health care needs and by racial/ethnic group. Method Using the 9-year data from Medical Expenditure Panel Survey, we examined associations between children's MH status and individual survey items or domains. We randomly split the data into two halves with the first half (training sample, n = 8611) used to identify promising items, and the second half (validation sample, n = 8779) used to calculate all statistical measures. After discovering significant predictors of children's MH status, we incorporated them into several brief markers of MH status. We also conducted stratified analyses by status of special health care needs and by racial/ethnic group. Results Less than half (48.7%) of the 8779 study children had a MH. The accessibility domain has stronger association with children's MH status (specificity = 0.84, sensitivity = 1, Kappa = 0.83) than other domains. The top two items with the strongest association with MH status asked about after-hours primary care access, including doctors' office hours at night or on the weekend and children's difficulty accessing care after hours. Both belong to the accessibility domain and are one of several reliable markers for children's MH status. While each of the two items did not differ significantly by status of special health care needs, there were considerable disparities across racial/ethnic groups with Latino children lagging behind other children. Conclusion Accessibility, especially the ability to access health care after regular office hours, appears to be the major predictor of having a MH among children. The ongoing efforts to promote the MH model need to target improving accessibility of health care after regular hours for children overall and especially for Latino children.